2016
DOI: 10.1097/01.asw.0000482834.94375.1e
|View full text |Cite
|
Sign up to set email alerts
|

Wound-Related Allergic/Irritant Contact Dermatitis

Abstract: Contact dermatitis to wound care products is a common, often neglected problem. A review was conducted to identify articles relevant to contact dermatitis.A PubMed English-language literature review was conducted for appropriate articles published between January 2000 and December 2015.Contact dermatitis is both irritant (80% of cases) or allergic (20% of cases). Frequent use of potential contact allergens and impaired barrier function of the skin can lead to rising sensitization in patients with chronic wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…For instance, PVA has been used to create hydrogels for wound dressing [ 29 ] or electrospun together with active substances, such as silver nanoparticles [ 30 ], and curcumin [ 31 ], to produce wound dressings. Several wound dressings in the market containing active agents such as hydrocolloids or silver dressings often used on wound healing have shown negative effects such as allergic contact dermatitis [ 32 ], and use of dressings loaded with antibiotics has risk of developing antimicrobial resistance [ 33 ]. Our interest in this study is to develop a dressing loaded with birch bark extract with a sustained drug release that is suitable for human use on wound healing with effective therapy even after long-term usage.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PVA has been used to create hydrogels for wound dressing [ 29 ] or electrospun together with active substances, such as silver nanoparticles [ 30 ], and curcumin [ 31 ], to produce wound dressings. Several wound dressings in the market containing active agents such as hydrocolloids or silver dressings often used on wound healing have shown negative effects such as allergic contact dermatitis [ 32 ], and use of dressings loaded with antibiotics has risk of developing antimicrobial resistance [ 33 ]. Our interest in this study is to develop a dressing loaded with birch bark extract with a sustained drug release that is suitable for human use on wound healing with effective therapy even after long-term usage.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to the development of irritative‐toxic, cumulative‐subtoxic, or contact‐allergic eczema . In a study by Alavi et al, it was shown that the irritative genesis of eczema in patients with chronic wounds is much more frequent (80%) than the contact‐allergic genesis (20%) . In the occurrence of contact‐allergic eczema, besides the widespread ingredients of care products such as fragrances, rosin, potassium dichromate, and also wound therapeutics such as hydrocolloids or hydrogels play a role .…”
Section: Discussionmentioning
confidence: 99%
“…To this end, various topical wound care products are available that provide a moist wound-healing environment, promote autolytic debridement, demonstrate anti-inflammatory activity and/or antimicrobial properties, and thereby promote an improved and rapid healing. 4 As wound healing can be delayed by microbial infection, topical antiseptics and antibiotic agents, including cadexomer and povidone iodine, chlorhexidine, polyhexanide (PHMB), octenidine, silver, and bacitracin, may be present to control microbial colonisation. 2,3,5 To prevent contamination of the dressing itself with mould, fungi, and/or bacteria and to protect consumers against an undesired increase in the risk of infection, preservation of such wound care formulations can be an additional prerequisite.…”
Section: Introductionmentioning
confidence: 99%
“…6 Similar to cosmetics and other personal care products, preservative ingredients, such as urea derivatives (imidazolidinyl and diazolidinyl urea), isothiazolinones (methylisothiazolinone and methylchloroisothiazolinone), halogen-organic actives (iodopropynyl butylcarbamate and methyldibromo glutaronitrile), formaldehyde, Quaternium 15 (ie, formaldehyde-releaser), silver salts, organic acids (potassium sorbate, sodium benzoate), phenoxyethanol (alone or in combination with methyldibromo glutaronitrile), and parabens, can be indispensable. 4,[6][7][8][9] Although the use of antimicrobial and preservative ingredients is, in turn, subjected to certain restrictions in order to safeguard both product and consumer safety, consumer awareness regarding their skin sensitisation potential has increased. Several agents, and paraben preservatives in particular, have been criticised in this regard.…”
Section: Introductionmentioning
confidence: 99%